Summary of Baseline Household Survey Results: Phonghong district Vientiane province Lao PDR - Tan Yen, Bui; Khodyhotha, Khamphamy; Toummavong, Phetsamone; Chidvilaphone, Saythong; Lee, Yong; Vorlasan, Sysavanh; Keophoxay, Anousith; Souvannaxayyavong, Chantha; Villanueva, Jerome; Ferrer, Alice J.; Pavelic, Paul; Sebastian, Leocadio S. (2015)
This report summarizes the results of the household baseline survey conducted in Ekxang Climate-Smart Village and six surrounding villages in Phonghong district, Vientiane province, Lao PDR. The survey was implemented with participation of 140 randomly selected households using pre-prepared tablet-based questionnaires. The majority of the households were male-headed. On average, each household had six members and most of the members were between 5 and 60 years old. The household size and labor force in the target region are similar to national average. The main source of food and income of the households were from on-farm agriculture production, which was mostly contributed by cultivation and livestock. Agriculture production was mainly for self-sufficient purpose as most of products were consumed within the household. Farm size mostly ranged between 1 and 5 hectares and households still can expand land for crops from existing pasture or fallow land. Besides their own land, households were also allowed access to communal land for food crops, vegetables, and other products. With the availability of arable land, food production was enough for the household demand throughout the year. Considering a “typical food year”, food shortage was only experienced by 3% of the households in June, July and October. Few households experienced food crisis in last five years. Although climate change is widely mentioned by the community, it was not perceived as a main factor that led to changes in farming practices. About 80% of the households changed their crops following market price and preference of consumer and availability of labor over the last 10 years. Rain water was often available for farming during rainy season. During the dry season, due to limited capacity of irrigation system, farmers often use water from ponds and boreholes for surrounding crop fields. Regarding information sources, households received climate and weather information from television and individuals, such as friends, relatives or neighbors. Most of the households owned television (97.9%) and mobile phone (95.7%). Information about extreme events and short term (2-3 days) weather forecast were available, but not the long term weather forecast or early warning of pest and disease outbreak. It seems that government organizations did not pay much attention to providing climate information to farmers as only one out of 129 households reported that they receive the information from government staffs.